Difference in force decay latex and non-latex elastic band based on duration of elastic use and salivary pH concentration: In vitro study - Rasdiana Bakri; Baharuddin M. Ranggang; Nasyrah Hidayati (Journal of Orthodontic Science)
OBJECTIVE: This study aimed to determine the difference in force decay between latex and non-latex elastic bands based on duration of use and salivary pH concentration. MATERIAL AND METHOD: The calculation of the sample size in this study used Federer. Total sample size is 80 and divided into four groups. First group consists of 20 elastic bands made from latex immersed in artificial saliva pH 5.2, second group consists of 20 elastic bands made from latex immersed in artificial saliva pH 6.7, third group consists of 20 elastic bands made from non-latex immersed in artificial saliva pH 5.2, and fourth group consists of 20 non-latex elastic bands immersed in artificial saliva pH 6.7. All samples were incubated at 37°C, and force magnitude was measured with a digital force gauge. RESULTS: The most force decay occurred in the first 24 hours when immersed in artificial saliva and was constant for up to 72 hours. The elastic band immersed in salivary pH concentration showed greater force decay compared with pH 6.7 both latex and non-latex. CONCLUSION: There was a significant difference in force decay of elastic bands made from latex and non-latex based on duration of elastic use. Force decay of elastic bands made from non-latex was greater than latex material. There was a difference in force decay elastic bands made from latex and non-latex based on the pH concentration of saliva. Force decay elastic band made from non-latex is greater than latex material and greater at pH 5.2 compared to 6.7.